Inventory of Medicinal Plants and Conservation Efforts among the Indigenous Community of Kedayon Village, Kemanisan Subdistrict, Curug District, Serang City - Fatimah Azahrah; Nabilah Artanti; Nurhasanah Nurhasanah; Aef Saefulloh; Desi Eka Nur Fitriana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Indonesia is a mega-biodiversity country with a wealth of medicinal plants and strong ethnobotanical knowledge among indigenous communities. However, modernization and the declining interest of the younger generation have caused traditional knowledge and the availability of medicinal plants to be increasingly threatened, including in Kedayon Village, Kemanisan Subdistrict, Curug District, Serang City. This study aims to: identify the types of medicinal plants used by the Kedayon Village community, describe how they are utilized in traditional medicine, and analyze forms of conservation efforts that can be implemented by the community in a sustainable manner. The method used is descriptive qualitative through field observation, documentation, and interviews. The results of the study identified 16 types of medicinal plants utilized from various plant parts such as leaves, roots, rhizomes, and seeds, with simple processing techniques such as boiling, squeezing, or steeping. These findings indicate that the community still relies on natural resources for traditional health needs. Recommended conservation efforts include community-based in-situ cultivation through home gardens and yards, accompanied by education and routine maintenance. These efforts are important to maintain the scarcity of medicinal plants while preserving local knowledge for future generations.